Global trends in disease burdens attributable to ambient and household air pollution: a comparative study of ten populous countries - Feng, Jing; Wang, Yannan; Meng, Xianghua; Fang, Yue (Frontiers in Public Health, 2025)
ObjectivesTo comparatively assess the disease burden attributable to ambient particulate matter (APM) and household air pollution (HAP) across the ten most populous countries between 1990 and 2021.MethodsData on disability-adjusted life years (DALYs) and age-standardized DALY rates (ASDRs) attributable to APM and HAP were obtained from the Global Burden of Disease Study 2021. Estimated annual percentage change (EAPC) was used to evaluate temporal trends. Quadratic regression models were applied to examine associations between socio-demographic index (SDI) and disease burden.ResultsFrom 1990 to 2021, global APM-related DALYs increased while ASDRs declined. In contrast, both DALYs and ASDRs attributable to HAP decreased markedly. Older adults experienced the highest APM-related burden, whereas children under five were most affected by HAP. Gender differences were also observed, with males generally showing higher burdens. SDI was strongly associated with HAP-related ASDRs (R2 = 0.88) but weakly associated with APM (R2 = 0.19).ConclusionSignificant disparities in air pollution-related disease burdens exist across countries and demographic groups. Clean energy policies, strengthened environmental regulations, and targeted interventions are essential to mitigate health impacts and advance global public health equity.